PKM2 controls cochlear development through lactate-dependent transcriptional regulation - Mingxuan Wu; Gaogan Jia; Yaoqian Liu; Yiyun Lou; Yunjie Li; Mingyu Xia; Huawei Li; Wenyan Li (Proceedings of the National Academy of Sciences, 2025)
Understanding the role of metabolic processes during inner ear development is essential for identifying targets for hair cell (HC) regeneration, as metabolic choices play a crucial role in cell proliferation and differentiation. Among the metabolic processes, growing evidence shows that glucose metabolism is closely related to organ development. However, the role of glucose metabolism in mammalian inner ear development and HC regeneration remains unclear. In this study, we found that glycolytic metabolism is highly active during mouse and human cochlear prosensory epithelium expansion. Using mouse cochlear organoids, we revealed that glycolytic activity in cochlear nonsensory epithelial cells was predominantly dominated by pyruvate kinase M2 (PKM2). Deletion of PKM2 induced a metabolic switch from glycolysis to oxidative phosphorylation, impairing cochlear organoid formation. Furthermore, conditional loss of PKM2 in cochlear progenitors hindered sensory epithelium morphogenesis, as demonstrated in PKM2 knockout mice. Mechanistically, pyruvate is generated by PKM2 catalysis and then converted into lactate, which then lactylates histone H3, regulating the transcription of key genes for cochlear development. Specifically, accumulated lactate causes histone H3 lactylation at lysine 9 (H3K9la), upregulating the expression of Sox family transcription factors through epigenetic modification. Moreover, overexpression of PKM2 in supporting cells (SCs) triggered metabolism reprogramming and enhanced HC generation in cultured mouse and human cochlear explants. Our findings uncover a molecular mechanism of sensory epithelium formation driven by glycolysis-lactate flow and suggest unique approaches for mammalian HC regeneration.